Microstructure evolution and plastic deformation of Ni47Co53 alloy under tension. Issue 4 (7th January 2022) - Ma, Rui-bo; Zhou, Li-li; Liang, Yong-chao; Tian, Ze-an; Mo, Yun-fei; Chen, Qian; Liu, Rang-su; Gao, Ting-hong; Xie, Quan
Abstract : During the tension process, single crystal and polycrystal bear plastic strain through stacking faults and grain boundaries, respectively. In addition metallic glass bears plastic strain through tacking faults and grain boundaries. Abstract : To investigate microstructural evolution and plastic deformation under tension, the rapid solidification processes of the Ni47 Co53 alloy are first simulated by molecular dynamics methods at cooling rates of 10 11, 10 12 and 10 13 K s −1 . Then, the uniaxial tension simulation study was conducted on a single crystal, polycrystal and metallic glass, which were formed during the rapid solidification. The results show that the dislocation loops evolution in the crystal is caused by the slips and proliferation of stacking faults, and in terms of plastic deformation, the single crystal is carried by stacking faults, while a polycrystal is carried by grain boundaries. A metallic glass formed at the critical cooling rate and crystallized under tension, the plastic deformation is carried by grain boundaries and stacking faults in metallic glass. Ultimately, the stacking faults are the most resistant to plastic deformation. This study has great significance for the study of the mechanical properties of single crystals, polycrystals and metallic glass.